2021
DOI: 10.1093/jnci/djab049
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Gaps in Cancer Survivorship Care: A Report From the 2019 National Cancer Institute Cancer Survivorship Workshop

Abstract: Today, there are more than 16.9 million cancer survivors in the United States; this number is projected to grow to 22.2 million by 2030. While much progress has been made in understanding cancer survivors needs and in improving survivorship care since the seminal 2006 Institute of Medicine report From Cancer Patient to Cancer Survivor: Lost in Transition, there is a need to identify evidence gaps and research priorities pertaining to cancer survivorship. Thus, in April 2019, the National Cancer Institute conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
60
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 75 publications
2
60
0
3
Order By: Relevance
“…The intersection of aging and cancer survivorship can be particularly difficult to navigate for people affected by cancer. Despite progress in supportive care for survivors, gaps still exist in addressing complex symptoms such as anxiety, pain, fatigue, insomnia, neuropathy, and cognitive dysfunction 40,41 . Moreover, the physical, emotional, and social ramifications of cancer may linger years after treatment, 42 further challenging the infrastructure and resources of health care systems 43 …”
Section: Global Cancer Burdenmentioning
confidence: 99%
“…The intersection of aging and cancer survivorship can be particularly difficult to navigate for people affected by cancer. Despite progress in supportive care for survivors, gaps still exist in addressing complex symptoms such as anxiety, pain, fatigue, insomnia, neuropathy, and cognitive dysfunction 40,41 . Moreover, the physical, emotional, and social ramifications of cancer may linger years after treatment, 42 further challenging the infrastructure and resources of health care systems 43 …”
Section: Global Cancer Burdenmentioning
confidence: 99%
“…Colorectal cancer (CRC) is the third most common human malignancy and the fourth crucial cause of cancerrelated death in worldwide [1][2][3][4][5][6]. CRC metastasis is the main cause of mortality in patients [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In general, findings from the network analyses were consistent with other recent efforts in identifying evidence gaps and setting cancer survivorship research priorities. 6 Another important point by Kemp et al 4 was the singleproblem/single-symptom approach used in most reviews, as evidenced by the low level of connectivity between domains and outcomes. Of note, these analyses were based on purely topical information and did not incorporate actual findings or strength of evidence from individual reviews in considering network connectivity, modularity, or other features.…”
mentioning
confidence: 99%
“…11 More recently, care coordination was identified as a key evidence gap in survivorship care in workshop of the National Cancer Institute. 6 Although research on care coordination is limited and robust measures are lacking, studies have demonstrated improved outcomes across the cancer care continuum, including better symptom control, more appropriate health care utilization, fewer medical errors, and decreased costs when care is well coordinated. 10,12 Given that care for breast cancer survivors often involves ongoing management from multiple specialist teams, care coordination is key.…”
mentioning
confidence: 99%